Essays on the housing market - Davids, Allan (School of Economics, 2023)
Housing represents the single most important asset, accounting for around 50% of global household wealth. At the household level, a house typically represents the largest asset most households will own through their lifetime. This is even more pronounced in emerging economies where household participation rates in real estate across the wealth distribution are higher than participation rates in financial assets. Most homes are purchased by means of a mortgage which typically constitutes the largest liability most households will have through their lifetime. Mortgages also make up a sizeable share of the asset base of banks. Moreover, the housing market is pivotal to the economy and the financial system, as illustrated by its central role in the Great Financial Crisis of 2007-2009. Despite this, the empirical housing literature in emerging markets is relatively underdeveloped relative to the literature in advanced economies. A major reason for this relates to the lack of detailed and reliable housing transaction data in emerging market economies. Leveraging a number of novel datasets, I explore two aspects of the housing market in Cape Town, South Africa, that are of academic and policy interest: foreign investment in the housing market and the discounts associated with home foreclosures. I document sizeable foreign investment in the housing market in Cape Town between 2011 and 2018, showing that these investors sort into the wealthier suburbs in the city that have had historically large communities of foreign inhabitants. Despite these sizeable net inflows, foreign ownership, has in fact, decreased throughout the sample period, highlighting that foreign buyers are not crowding out local buyers. Turning to purchase and investment outcomes, I find that foreign buyers and sellers realize worse outcomes than local buyers and sellers, purchasing otherwise identical properties for a premium, leading to lower returns upon resale. This result can partly be explained by wealth effects and information asymmetries. I also highlight an important feature of foreign demand, so far overlooked by the existing literature: the tendency of foreign buyers to be cash buyers. I show that failing to control for the financing choices of the buyer leads to a sizeable underestimate of the foreign buyer premium driven by the fact that buyers who purchase properties using cash as opposed to a mortgage typically attract a sizeable discount. In the following chapter, I examine the relationship between exchange rate depreciations and foreign non-resident investment in the housing market. I show that foreign non-resident transactions increase following exchange rate depreciations and are also increasing in the size of the depreciation. I find no evidence of similar effects for foreign born permanent residents in South Africa, highlighting that the exchange rate effect is linked to purchasing property in foreign currency and not to whether or not the buyer is a foreigner. I then use large and sudden exchange rate depreciations as a positive exogenous shock to foreign non-resident demand to study the effect of foreign non-resident investment on house prices, leveraging an identification strategy that compares quality adjusted prices in geographically close suburbs that differ in their ex-ante attractiveness to foreign non-residents, and find a positive causal effect of foreign non-resident demand. While this may raise concerns about the impact of foreign non-resident demand on the affordability of homes for local buyers, the fact that foreign non-resident investment in housing appears to be counter-cyclical, increasing following large depreciations, suggests that these inflows may have important stabilizing effects on house prices. Finally, I document the extent of home foreclosures in Cape Town and estimate the discounts that these properties sell for. Leveraging features of the institutional setting I study and the data I employ, I am able to provide a more complete characterization of the dynamics affecting foreclosure discounts by disentangling the foreclosure discounts when foreclosures sell at a foreclosure auction from the discounts that arise when these foreclosures sell in the private market outside of the auction. I find evidence that foreclosure discounts are substantial both in the private non-auction market and when sold at an auction. In the former, the discounts can be rationalized as a classic firesale discount driven by the financial distress of the seller. In the latter, I present evidence that limited competition at auctions driven by costs to participation could rationalize the foreclosure discounts at auctions, consistent with housing search theory. I also conduct an extensive robustness exercise to account for potential factors which could lead to an upward bias in the estimated foreclosure discount showing how various factors confound the true foreclosure discount.